EFEKTIVITAS MINYAK JARAK PAGAR SEBAGAI LARVASIDA, ANTI-OVIPOSISI DAN OVISIDA TERHADAP LARVA NYAMUK - Endang Puji Astuti; Adi Riyadhi; Noor Roufiq Ahmadi (Buletin Penelitian Tanaman Rempah dan Obat, 2011)
Effectiveness of Castor Oil as a Pagar Larvasida, oviposition and anti-Mosquito Larva of Ovisida Aedes albopictusAedes albopictus mosquito is increasing problem of public health, being the vector responsible for Chikungunya and the second vector for Dengue. Various efforts have been done to control the mosquitoes both chemically and naturally. Jatropha curcas seed oil was known to posses insecticide activity against larval mosquito species. The study aimed to examine effectiveness of J. curcas seed oil as larvi-cidal, anti-oviposition, and ovicidal against A. albopictus. The larval mortality was observed after 24 h of exposure. The LC50 value of J. curcas seed oil is 905.29 ppm, against A. albopictus. The oil significantly (p <0.05) reduced oviposition by A. albo-pictus in the 0.4 and 0.5% concentration for J. curcas. J. curcas seed oil was ef-fecttive on 0.4 and 0.5% concentration so that could prevent the eggs from being hatched. Quantitative analysis of J. curcas by spectrophotometer revealed the pre-sence of piperine, its potential against lar-val mosquito. The result of this study sug-gested that the J. curcas oil posses insec-ticide properties.